2006
DOI: 10.1002/pmic.200500502
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicles of the VA‐MENGOC‐BC® vaccine against serogroup B of Neisseria meningitidis: Analysis of protein components by two‐dimensional gel electrophoresis and mass spectrometry

Abstract: Neisseria meningitidis is a Gram-negative bacterium responsible for significant mortality worldwide. While effective polysaccharides-based vaccines exist against serogroups A, C, W135, and Y, no similar vaccine is suitable for children under 4 years against disease caused by serogroup B strains. Therefore, major vaccine efforts against this serogroup are based on outer membrane vesicles (OMVs), containing major outer membrane proteins. The OMV-based vaccine produced by the Finlay Institute in Cuba (VA-MENGOC-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 67 publications
2
45
0
1
Order By: Relevance
“…The second ABC transporter, NMB0634 (FbpA), is a virulence factor with a role in iron uptake (42); however, the role for the third ABC transporter, NMB1612, is unknown despite its presence in OMV and OM preparations (59). The other hypothetical protein associated with the periplasm, NMB0928, has been reported to be present as a constituent of OMV derived from N. meningitidis (52,53,55,59) and N. lactamica (53) and also to be conserved across many meningococcal serogroups and capable of inducing murine bactericidal antibodies (8). The thiol-disulfide interchange protein DsbC is potentially interesting as a vaccine candidate due to function, as it catalyzes the formation of disulfide bonds essential for the conformational stability and folding of proteins, and recently, the DsbC-encoding open reading frame has been reported to become upregulated in meningococci during infection of HeLa cells (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second ABC transporter, NMB0634 (FbpA), is a virulence factor with a role in iron uptake (42); however, the role for the third ABC transporter, NMB1612, is unknown despite its presence in OMV and OM preparations (59). The other hypothetical protein associated with the periplasm, NMB0928, has been reported to be present as a constituent of OMV derived from N. meningitidis (52,53,55,59) and N. lactamica (53) and also to be conserved across many meningococcal serogroups and capable of inducing murine bactericidal antibodies (8). The thiol-disulfide interchange protein DsbC is potentially interesting as a vaccine candidate due to function, as it catalyzes the formation of disulfide bonds essential for the conformational stability and folding of proteins, and recently, the DsbC-encoding open reading frame has been reported to become upregulated in meningococci during infection of HeLa cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…The use of gel-based liquid chromatography-tandem mass spectrometry (LC-MS-MS), in which electrophoretic separation of proteins according to molecular weight is followed by LC-MS-MS, has revealed that both meningococcal OM and OMV preparations contained a larger number of proteins than have been previously detected by conventional one-dimensional (1-D) sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) separation (59). OMV vaccine preparations have been revealed to be similarly complex by two-dimensional (2-D) gel electrophoresis (52,54).…”
mentioning
confidence: 99%
“…These studies did not achieve high-throughput proteomics and identified only a small number of well-known proteins, except for E. coli-derived OMVs . In contrast to native OMVs, several proteomic studies have been performed on detergent-extracted OMVs (DOMVs), which are made from whole bacteria with a detergent treatment (Nally et al, 2005;Ferrari et al, 2006;Uli et al, 2006;Vipond et al, 2006). Since outer membrane proteins and LPS of OMVs can induce a host immune response, DOMVs from pathogenic strains are promising vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, OMVs may provide a survival advantage between competing species by virture of their bacteriocidal activity (27)(28)(29). OMVs also show promise as vaccine antigen platforms, given their composition and physico-chemical properties (30)(31)(32)(33)(34). For example, OMVs of V. cholerae have been shown to induce protective immunity in experimental animals (35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…Various approaches have been used to characterize the protein content of OMVs from different human pathogens, including 1-and 2-dimensional electrophoresis (1-DE and 2-DE) (30,32,33) coupled with mass spectrometry (MS) (25,31,34). Liquid chromatography coupled with MS (LC-MS/MS) has also been applied to define proteins associated with OMVs (42) but only in a limited fashion and never fully coupled with systematic genetic analysis for the role of OMV proteins in virulence or bacterial growth and survival.…”
mentioning
confidence: 99%